Control of electron beam polarization in the bubble regime of laser-wakefield acceleration. (1st August 2022) - Fan, H C; Liu, X Y; Li, X F; Qu, J F; Yu, Q; Kong, Q; Weng, S M; Chen, M; Büscher, M; Gibbon, P; Kawata, S; Sheng, Z M
Abstract: Electron beam polarization in the bubble regime of the interaction between a high-intensity laser and a longitudinally pre-polarized plasma is investigated by means of the Thomas–Bargmann–Michel–Telegdi equation. Using a test-particle model, the dependence of the accelerated electron polarization on the bubble geometry is analysed in detail. Tracking the polarization dynamics of individual electrons reveals that although the spin direction changes during both the self-injection process and acceleration phase, the former has the biggest impact. For nearly spherical bubbles, the polarization of electron beam persists after capture and acceleration in the bubble. By contrast, for aspherical bubble shapes, the electron beam becomes rapidly depolarized, and the net polarization direction can even reverse in the case of a oblate spheroidal bubble. These findings are confirmed via particle-in-cell simulations.